Early Eocene Thermal Maximum 3: Biotic Response at Walvis Ridge (SE Atlantic Ocean). Issue 8 (4th August 2018) - Thomas, Ellen; Boscolo‐Galazzo, Flavia; Balestra, Barbara; Monechi, Simonetta; Donner, Barbara; Röhl, Ursula
Abstract: We combine stable isotope, calcareous nannoplankton, and benthic foraminiferal records for Ocean Drilling Program Sites 1262 (paleodepth ~3, 500 m) and 1263 (paleodepth ~1, 500 m) on Walvis Ridge (SE Atlantic), to document the marine biotic response to Eocene Thermal Maximum 3, in the early part of the Early Eocene Climate Optimum, ~3.1 Myr after the Paleocene/Eocene Thermal Maximum. Bottom water warming may have decreased the vertical thermal gradient at both sites, but more at Site 1263 than at Site 1262. Floral and faunal changes were more muted at Site 1262 than at shallower Site 1263, indicating that carbonate dissolution was not the most important cause of biotic effects. Assemblage changes were more pronounced in benthos than in plankton. Calcareous nannofossils underwent minor ecological changes, possibly related to the presence of warmer waters, especially at Site 1263, and dissolution‐resistant taxa increased in abundance. Benthic foraminiferal diversity decreased at both sites, but benthic foraminiferal accumulation rates declined dramatically at Site 1263, remaining stable at Site 1262. Ocean circulation may have changed during ETM3, resulting in the presence of a warmer (intermediate) water mass at Site 1263. More pronounced warming may have caused enhanced remineralization of organic matter, so less food reached the benthos. The biotic response to the X‐event was less pronounced than that to earlier and more severe hyperthermal events, the Paleocene/Eocene Thermal Maximum and Eocene Thermal Maximum 2. The extent of the biotic response reflects the severity of the environmental disturbance but varies by location (e.g., paleodepth on Walvis Ridge). Plain Language Summary: We can learn about the effects of future global warming on oceanic life forms by studying records of global warming episodes in the past. We studied a global warming episode ~52.8 million years ago, when the world was much warmer than today (e.g., no ice sheets on Antarctica). We used samples collected by the International Ocean Discovery Program through deep‐sea drilling in the Southeast Atlantic, at two sites (~1, 500 and ~3, 500‐m water depth at the time of the events). We investigated calcareous, microscopic fossils formed by one‐celled, plant‐like organisms (photosynthesizers) floating in the upper waters and microscopic fossils of one‐celled animal‐like organisms, which lived on and in mud on the seafloor. We analyzed their shells chemically, using that information to reconstruct water temperatures. We noted that seafloor organisms suffered more change during the global warming than surface dwellers, especially at the shallower site, where waters warmed more than at greater depth. The effects on life forms were mainly caused by the warming itself, which influences how much food the organisms need, so that organisms in the warmest waters were relatively starved. We compared our data with those on other periods of global warming and concluded that more severe warming generally resulted in more severe effects on ocean life. Key Points: We reconstruct ecological and environmental changes across Eocene Thermal Maximum 3 in the SE Atlantic Stable isotope and microfossil analysis shows that warming and ecological change were more marked at intermediate than at greater depth Circulation changes and/or greater relative warming at high latitudes could have produced this pattern